Major depression and clinical outcomes in patients with heart failure with preserved ejection fraction. (30th December 2020) - Liu, Jian; Guo, Zejun; Fan, Meida; Liang, Weihao; He, Xin; Wu, Dexi; Dong, Yugang; Zhu, Wengen; Liu, Chen
Abstract: Objective: Limited data have been published concerning about depression in heart failure with preserved ejection fraction (HFpEF). Besides, among HFpEF patients with depression, the efficacy of antidepressants is poorly defined. Therefore, our current study was aimed to examine the relationship between major depression and clinical outcomes in HFpEF patients and further address the effects of antidepressants on prognosis in patients with major depression and HFpEF. Methods: A total of 1431 patients enrolled in the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist Trial (TOPCAT) were divided into 2 groups according to the baseline depression status. Major depression was diagnosed if the Patient Health Questionnaire‐9 score (PHQ‐9) ≥ 10. Univariable and multivariable Cox proportional hazards models tested the association of major depression with outcomes and the effects of antidepressants among HFpEF patients with major depression during a follow‐up of 6 years. Results: 26.7% (382/1431) of patients were diagnosed with major depression. After multivariable adjustment, major depression at baseline was not significantly associated with cardiovascular outcomes (fully adjusted hazard ratio (aHR) 0.95 [0.76‐1.18] for primary outcomes; aHR: 0.86 [0.67‐1.10] for HF hospitalization; aHR: 1.06 [0.91‐1.23] for any hospitalization; aHR: 1.00 [0.70‐1.43] for cardiovascular death; aHR: 1.24 [0.96‐1.61] for all‐cause death). Additionally, among HFpEF patients with major depression, the use of antidepressants was not associated with adverse events ( P > .05 for all analyses). Conclusions: In HFpEF patients, major depression at baseline did not increase mortality or rehospitalization. Additionally, treatment with antidepressants might not improve prognosis among HFpEF patients with major depression. Future studies are warranted to explore the effects of antidepressants on HFpEF patients with depression.